Hypertension, augmented activity of matrix metalloproteinases-2 and -9 and angiogenic imbalance in hypertensive pregnancy are attenuated by doxycycline - Nascimento, Regina A. [UNESP]; Possomato-Vieira, José S. [UNESP]; Gonçalves-Rizzi, Victor H. [UNESP]; Bonacio, Gisele F.; Rizzi, Elen; Dias-Junior, Carlos A. [UNESP] (My University, 2018)
Preeclampsia is manifested as maternal hypertension and fetal growth restriction. Matrix metalloproteinases (MMPs) are involved in hypertension and doxycycline reduces blood pressure by inhibition of MMPs. Moreover, excessive levels of MMPs and reduced nitric oxide (NO) bioavailability have been related to preeclampsia. We investigated the involvement of MMPs in hypertension in pregnancy induced by Nω-Nitro-L-arginine methyl ester (L-NAME) in rats. To this end, zimography was performed to evaluate the activity of MMPs -2 and -9 in placenta, uterus and thoracic aorta, and systolic blood pressure, feto-placental development and metabolites of NO were evaluated. Also, plasma antioxidant capacity, plasma levels of soluble fms-like tyrosine kinase-1 (sFlt-1) and placental growth factor (PLGF) were examined. Doxycycline prevented hypertensive pregnancy and significant reductions in number of pups induced by L-NAME. Low NO bioavailability was found in hypertensive pregnant rats treated (or not) with doxycycline. Increased activity of placental MMP-2 and MMP-9 and uterine MMP-2 were attenuated by doxycycline. MMP-2 activity of thoracic aorta showed no change after hypertension. Increases in PLGF with concomitant decreases in sFlt-1 levels were found with doxycycline treatment. Also, plasma antioxidant capacity was improved with doxycycline. Also, elevations of plasma antioxidant capacity were observed in hypertensive rats treated with doxycycline. Therefore, we suggest that L-NAME reduced NO and this triggered the increases in MMP-2 and -9 activities during hypertensive pregnancy. Importantly, increases in MMPs activation and angiogenic imbalance were attenuated by doxycycline and these effects were associated with decreases in systolic blood pressure.
Keywords: Doxycycline; Hypertensive pregnancy; Metalloproteinases; Nitric oxide; Rats